Comparison of Permanent-Magnet Assisted Synchronous Reluctance Motors with Different Rotor Structures - Boztas, Gullu; Aydogmus, Omur (Ieee, 2019)
This paper presents a comparison of synchronous reluctance motors with different rotor structures which are assisted with or without permanent magnets. Firstly, a conventional synchronous reluctance motor (SynRM) structure was designed in order to obtain a base motor structure for the other motors designed in this study. Then, three different motor types were designed by using the base motor structure which has 9 stator slots and 4 flux barriers on the rotor. The ceramic magnets were placed in different positions of the rotor flux barriers. The performances of the designed SynRM and PMa-SynRMs were analyzed in terms of torque, speed and efficiency. In addition, the flux distributions of designed motors were analyzed by using MotorSolve program. The effects of the position and amount of the magnets on the rotor flux barriers were analyzed for designed rotor structures.
11th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 28-30, 2019 -- Bursa, TURKEY
Keywords: Ferrite Magnets; Low-Cost; Design; Performance; Optimization; Pm; Pmasynrm